Practice of young generations on traditional Javanese-Malay foods in Selangor / Nurul Falah Hashim ... [et al.] - Hashim, Nurul Falah; Abdull Samat, Muhamad Arif Azrai; Ishak, Noriza; Md Sahak, Adibah Aishah (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2024)
The Malay ethnic group, with deep historical ties to the region, traces its roots back to the early Malay Sultanate of Malacca. Over time, this community evolved into various sub-ethnic groups, each contributing unique traditions and practices to Malaysia's multicultural landscape. Malaysia, renowned as a cultural and culinary paradise, boasts a rich food heritage shaped by diverse ethnic influences. Nevertheless, the impact of globalisation and contemporary communication has significantly transformed local lives and views, especially regarding traditional meals. The objective of this research is to investigate the impact of dynamics on preserving of practices among young Javanese. The study comprised 103 young individuals of Javanese-Malay descent residing in Selangor. The analyses consisted of descriptive analysis and Spearman correlation analysis. It indicates that knowledge, food images, and culinary experiences have a substantial influence on traditional food choices within the Javanese-Malay group. The lifestyles of the younger generation are changing due to globalisation, technical developments in food production, and time barriers. As a result, there is a clear decrease in the recognition and consumption of traditional foods. It is crucial to make significant efforts to enhance and safeguard Malaysia's diverse culinary traditions to reinforce the country's national identity.